Evaluation of different electrochemical methods on the oxidation and degradation of Reactive Blue 4 in aqueous solution - Carneiro, P. A.; Osugi, M. E.; Fugivara, Cecilio Sadao [UNESP]; Boralle, N.; Furlan, Maysa [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier B.V., 2005)
The oxidation of a reactive dye, Reactive Blue 4, RB4, (C.I. 61205), widely used in the textile industries to color natural fibers, was studied by electrochemical techniques. The oxidation on glassy carbon electrode and reticulated vitreous carbon electrode occurs in only one step at 2.0 < PH < 12 involving a two-electron transfer to the amine group leading to the imide derivative. Dye solution was not decolorized effectively in this electrolysis process. Nevertheless, the oxidation of this dye on Ti/SnO2/SbOx (3% mol)/RuO2 (1% mol) electrode showed 100% of decolorization and 60% of total organic carbon removal in Na2SO4 0.2 M at PH 2.2 and potential of +2.4 V. Experiments on degradation photoelectrocatalytic were also carried out for RB4 degradation in Na2SO4 0.1 K PH 12, using a Ti/TiO2 photoanode biased at +1.0 V and UV light. After 1 h of electrolysis the results indicated total color removal and 37% of mineralization. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: anthraquinone dye; reactive dyes; electrochemical oxidation; photoelectrocatalysis; Reactive Blue 4